2008
DOI: 10.1002/ijc.23852
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of efficacy for 5‐FU‐based treatments in advanced colorectal cancer: mRNA expression for 18 chemotherapy‐related genes

Abstract: 5‐Fluorouracil (5‐FU)‐based regimens remain a cornerstone in the treatment of colorectal cancer (CRC). However, the attendant toxicity prevents these regimens from reaching maximum therapeutic potential. In this retrospective analysis, we examined the pretreatment expression of 18 genes in archival tumor bank samples from patients with advanced CRC to determine if one or more of the selected genes showed promise as either a prognostic or predictive marker of 5‐FU‐based treatment outcomes. One hundred and forty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 39 publications
(53 reference statements)
2
22
0
Order By: Relevance
“…Previously, we identified TP gene expression in microdissected tumour samples from colorectal carcinomas as a possible predictor of chemotherapy response and survival in advanced colorectal cancer [12]. This finding was in keeping with the observations of other independent reports [12-15].…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previously, we identified TP gene expression in microdissected tumour samples from colorectal carcinomas as a possible predictor of chemotherapy response and survival in advanced colorectal cancer [12]. This finding was in keeping with the observations of other independent reports [12-15].…”
Section: Introductionsupporting
confidence: 90%
“…This finding was in keeping with the observations of other independent reports [12-15]. In the present study, we included tumour-associated stromal cells in our analysis of TP gene expression, because the majority of expression appears to be associated with TAMs.…”
Section: Introductionsupporting
confidence: 87%
“…In addition, elevated intratumoural DPD expression results in an increased fluoropyrimidine catabolism at the expense of anabolism, and may cause fluoropyrimidine resistance, as recently shown by others (Gustavsson et al , 2009) and us at the preclinical (Beck et al , 1994) and clinical levels (Etienne et al , 1999). Two randomized trials of 5FU-based adjuvant therapy vs no treatment have reported that stage II–III patients bearing dMMR tumours do not benefit from 5FU-based therapy (Ribic et al , 2003; Sargent et al , 2010).…”
Section: Discussionmentioning
confidence: 74%
“…TP and TS expressions were found to be independent variables in these tumours, so that low expression levels of both TS and TP in tumours predicted a high response rate to 5-FU/LVas well as a significantly longer survival, whereas none of the patients with high expression of either TP or TS were responders [58]. In another study, Gustavsson et al retrospectively examined the pretreatment expression of TP and other 17 genes in archival tumour samples from patients with advanced CRC to determine if one or more of the selected genes can be used as either a prognostic or predictive marker of 5-FU-based treatment outcomes [59]. One hundred and fortyfour CRC patient samples were analysed via real-time PCR for gene expression.…”
Section: Tp As a Predictive Biomarkermentioning
confidence: 99%